Usage of Video Streaming Platforms and its impact on Incidental learning of Alpha Kids: A Systematic Review-based Investigation - Mirza, Ayesha; Riaz, Saqib (Journal of Peace, Development and Communication, 2024)
Today when mobile phones and tablets are popular media devices, traditional television is replaced by Video Streaming Platforms (VSPs), i.e., Netflix Kids, Disney-Hoter, and YouTube Kids, particularly among 8 to 11-year-olds. Research indicates that these platforms cater to children’s needs effectively. This study reviewed the literature on VSPs and incidental learning among children published in the past thirteen years. The results revealed that children primarily use VSPs because they offer flexibility, convenience, and competitive pricing, making them the preferred choice. These platforms are designed to meet children’s needs and desires, including maintaining a positive mood and seeking stimulation. They also allow users to discover new content, improving their viewing experience. Exposure to diverse characters and narratives positively influences children’s attitudes toward different cultures and identities, promoting inclusivity. Moreover, these platforms offer educational opportunities beyond conventional boundaries, enabling children to access knowledge and learning experiences. Incidental learning through platforms allows children to engage with interesting topics quickly. Thus, it is concluded that despite the importance of video streaming platforms, parents and caretakers must guide children’s social media usage and ensure age-appropriate content to ensure optimal benefits for their learning, well-being, and overall development.